Comparative Analysis: Global Rating Scale vs. Checklist in Teaching and Assessing Skill Competence - Somia Saghir; Bushra Sultan; Farhana (ziauddin University, 2024)
This study compared the effectiveness of the Global Rating Scale (GRS) versus the checklist for teaching and evaluating nursing students on two skills; nasogastric tube (NGT) and subcutaneous injection. Using a census sample, 100 students of 2nd year Bachelor of Science in Nursing (BSN) were enrolled and divided into two groups. The control group was taught and evaluated on the traditional checklist, whereas the experimental group through the GRS. The results showed students in the experimental group obtained a higher mean score (NGT 9.41, subcutaneous injection 9.27) than the control group (NGT 7.2, subcutaneous injection 7.6). Likewise, critical point scores were also notably higher in the experimental group (NGT 9.6, subcutaneous injection 9.8) than in the control group (NGT 1.7, subcutaneous injection 2.4). GRS is recommended for teaching and evaluating nursing students' psychomotor skills. Educator training is essential for effective GRS utilization, enhancing performance evaluation, ensuring competence, and aligning with study program objectives for enhanced patient safety.